MODELING AND COMPARISON OF IP AND FUZZY-PI REGULATORS OF SPEED CONTROL OF DFIM FOR SUPPLY OF POWER TO THE ELECTRICAL NETWORK - Guediri, A.; Ben Attous, D. (University of Eloued جامعة الوادي, 2018)
This paper presents a comparison between a fuzzy logic controller and a conventional IP controller used for speed control with a direct stator flux orientation control of a doubly fed induction. The effectiveness of the proposed control strategy is evaluated under different operating conditions such as of reference speed and for load torque step changes at nominal parameters and in the presence of parameter variation. Simulation results show that the fuzzy logic controller is more robust than a conventional IP controller against parameter variation and uncertainty, and is less sensitive to external load torque disturbance with a fast dynamic response; the stator side power factor is controlled at unity level. Then, an intelligent artificial fuzzy control of a wind energy system based on DFAM for supply of power to the electrical network. Its simulated performances are then compared to those of a classical PI controller. Specifically fuzzy systems are created to overcome the disadvantages of fuzzy systems. Results obtained in Matlab/Simulink environment show that the fuzzy control is more robust, have superior dynamic performance and hence found to be a suitable replacement of the conventional PI controller for the high performance drive applications.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Doubly fed asynchronous machine (DFAM); Field oriented control; Fuzzy control, Fuzzy PI controller, conventional IP controller.